Peran Kantor Urusan Agama dalam Menciptakan Keluarga Sakinah - Palwi Rakhman (Al-Mizan (e-Journal), 2021)
Every married couple hopes that their home life will be created as a family that is confident and full of love. This article will discuss the role of the Office of Religious Affairs (KUA) in creating happy families. This research is library research which is analyzed by qualitative descriptive. The approach used is a sociological legal approach. The results showed that the Office of Religious Affairs (KUA) made efforts to foster happy families through religious education in the family, religious education in the community, religious education through educational institutions, bridal brokering courses, family counseling, fostering adolescents of marriage age, empowering family economies and improving nutrition. family.